1977
DOI: 10.1136/bmj.2.6102.1567
|View full text |Cite
|
Sign up to set email alerts
|

Psychological and social evaluation in cases of deliberate self-poisoning admitted to a general hospital.

Abstract: In a prospective clinical trial 312 cases of self-poisoning (276 patients) consecutively admitted to hospital were randomly allocated to medical teams or to psychiatrists for an initial psychiatric assessment and a decision as to "disposal." Junior doctors and nurses received some instruction in this work. Both groups of assessors asked for help from social workers when necessary. Once the medical teams had completed their assessments, psychiatrists provided most of the hospital treatment. Follow-up at one yea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0
1

Year Published

1982
1982
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(23 citation statements)
references
References 5 publications
2
20
0
1
Order By: Relevance
“…However, despite these difficulties, a number of studies have shown that acceptable rates are possible with attempted suicides. As mentioned above, Greer and Bagley (1971) followed up 97% of their 211 patients; Gardner et al . (1977) traced 85% of the patients in their study at 12 months; Hawton et al .…”
Section: Follow‐upmentioning
confidence: 97%
See 1 more Smart Citation
“…However, despite these difficulties, a number of studies have shown that acceptable rates are possible with attempted suicides. As mentioned above, Greer and Bagley (1971) followed up 97% of their 211 patients; Gardner et al . (1977) traced 85% of the patients in their study at 12 months; Hawton et al .…”
Section: Follow‐upmentioning
confidence: 97%
“…However, randomization is feasible, and has been successfully carried out in a number of studies (e.g., Chowdhury et al ., 1973; Gardner, Hanka, O'Brien, Page, & Rees, 1977; Gibbons, Butler, Urwin, & Gibbons, 1978; Hawton, Bancroft, Catalan, Kingston, Stedeford, & Welch, 1981; Liberman & Eckman, 1981; Termansen & Bywater, 1975; Welu, 1977). Indeed, it is felt within the research community that the increased difficulty and cost of the RCT are outweighed by the confidence that clinicians can put in their findings, in comparison to results from other types of trials.…”
Section: Random Assignment To Treatmentmentioning
confidence: 99%
“…Finkle (1984) claimed that the overall reduction in prescriptions for dextropropoxyphene in the US could not account for the relatively larger fall in fatal overdoses, and he suggested that doctors had become particularly wary of prescribing dextropropoxy-phene to patients considered to be 'at risk' of selfpoisoning, but had continued to prescribe the drug for other patients. This 'at risk' group are typically female, experience relative social isolation, have known marital problems or difficulty with interpersonal relationships, drug or alcohol dependency and a past history of deliberate self-poisoning or other previous psychiatric history (Gardener et al 1977).…”
Section: Preventionmentioning
confidence: 99%
“…Von jenen, denen ambulante psychiatrische Behand lung vorgeschlagen wurde, ergriffen 43% diese Möglichkeit nicht. Gardner et al [1977] wiesen nach, dass die Übernahmeder Betreuung durch Psych iater zumindest über einen Zeitraum von 1 Jahr nach dem Suizidversuch zu keinem Unterschied gegenüber der nicht nachbetreuten Gruppe hinsicht lich der Rückfallhäufigkeit führt.…”
Section: Nachbetreuungunclassified